Associations of educational attainment and cognitive level of job with old age verbal ability and processing speed: The mediating role of chronic diseases. Issue 4 (4th July 2018) - Ihle, Andreas; Oris, Michel; Fagot, Delphine; Chicherio, Christian; van der Linden, Bernadette W. A.; Sauter, Julia; Kliegel, Matthias
ABSTRACT: We investigated whether the relation of educational attainment and cognitive level of job to performance in verbal ability and processing speed in old age was mediated via the number of chronic diseases. A total of 2, 812 older adults participated. Psychometric tests on verbal ability and processing speed were administered. Individuals were interviewed regarding their education, midlife occupation, and chronic diseases in old age. Higher educational attainment and higher cognitive level of job were correlated with better performance in verbal ability and processing speed (.15 ≤ r ≤ .33, p s < .001). 1.4 to 7.3% of these relations was mediated via the number of chronic diseases ( β = .01, p s < .026). In conclusion, individuals with higher educational attainment and higher cognitive level of job may possibly suffer from fewer chronic diseases later in life. Possibly, this may finally be related to better performance in verbal ability and processing speed in those individuals in old age.